The role of Sb-over-Te ratio on the structural evolution of GeSbTe phase-change materials - O. Daoudi; E. Nolot; M. Bernard; M. Dartois; M. Tessaire; L. Fellouh; J. Li; N. Bernier; F. Fillot; V.-H. Le; H. Renevier; G. Navarro (Scientific Reports)
Abstract Phase-change memory is a mature technology suitable for next generation of non-volatile memory, meeting the strict requirements of embedded applications. This was achieved by the stoichiometry tuning of GeSbTe (GST) alloy, enhancing the stability of the programmed states at high temperatures. However, the structural properties become more complex for compositions outside the Sb2Te3-GeTe pseudo-binary line. We have previously studied the effects of Ge introduction in Ge2Sb2Te5 alloy highlighting its structural evolution, segregation and crystallization kinetics at high temperature. In this work, for the first time to our knowledge, we combine complementary techniques to study the effects of antimony over tellurium ratio (Sb/Te) on the crystallization kinetics of different GST systems. We highlight that increasing the Sb/Te ratio increases Sb-Te bond lengths and lattice parameters, at the same time leading to a higher crystalline growth speed than in low Sb/Te ratio based compositions. Thus, Sb/Te ratio determines the structural and crystalline parameters of GST crystalline phases. Finally, in the light of these results, we demonstrate that in more complex Ge-rich GST alloys characterized by a high thermal stability of the amorphous phase, the Sb/Te ratio still drives the stoichiometry of the segregated GST phases. Such understandings provide a key for further developing future Phase-change materials for embedded applications.